Cytotoxic effects of new MTA-based cement formulations on fibroblast-like MDPL-20 cells - Roberti Garcia, Lucas da Fonseca [UNESP]; Santos, Alailson Domingos dos [UNESP]; Silos Moraes, Joao Carlos [UNESP]; Souza Costa, Carlos Alberto de [UNESP] (Sociedade Brasileira De Pesquisa Odontologica, 2016)
The present study aimed at evaluating the cytotoxic effects of a novel cement called CER on periodontal fibroblast-like cells of mice (MDPL-20), in comparison with different formulations of Mineral Trioxide Aggregate (MTA), by means of the cell viability test (MTT) and cell morphology analysis. Thirty-two round-shaped samples were fabricated with the following cements: white MTA, white and gray CER and experimental white MTA. The samples were immersed in serum-free culture medium for 24 hours or 7 days (n = 16). The extracts (culture medium + components released from the cements) were applied for 24 hours to previously cultured cells (40.000 cells/cm(2)) in the wells of 24-well plates. Cells seeded in complete culture medium were used as a negative control. Cell viability was assessed using the MTT assay. Two samples of each cement were used for cell morphology analysis by Scanning Electron Microscopy (SEM). The extracts obtained at the 7-day period presented higher cytotoxicity compared with the 24-hour period (p < 0.05). The gray CER obtained at 24 hours presented the highest cytotoxic effect, whereas the experimental white MTA presented the lowest, similar to the control (p > 0.05). However, at the 7-day period, the experimental white MTA presented no significant difference in comparison with the other cements (p > 0.05). At the 7-day period, CER cement presented cytotoxic effects on fibroblast-like cells, similar to different MTA formulations. However, the immersion period in the culture medium influenced the cytotoxicity of the cements, which was greater for CER cement at 24 hours.
Keywords: Biocompatible Materials; Dental Materials; Endodontics; Silicate Cement